2018
DOI: 10.5500/wjt.v8.i6.232
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of transplant renal artery pseudoaneurysm using expandable hydrogel coils: A case report and review of literature

Abstract: Transplant renal artery (TRA) pseudoaneurysm can result in bleeding, infection, graft dysfunction and graft loss. We report the management of a renal transplant recipient who presented five months after renal transplantation with deterioration of renal function, who was found to have TRA pseudoaneurysm and TRA stenosis. Both were treated radiologically by using expandable hydrogel coils (EHC) in combination with stenting. Improvement in clinical, biochemical and radiological parameters were observed after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…16 Multiple cases have reported elevated, stenotic velocities at the renal artery origin, adjacent to the pseudoaneurysm. 15,18 It has been suggested that this might be caused by transplant renal artery compression from the adjacent pseudoaneurysm. 18…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Multiple cases have reported elevated, stenotic velocities at the renal artery origin, adjacent to the pseudoaneurysm. 15,18 It has been suggested that this might be caused by transplant renal artery compression from the adjacent pseudoaneurysm. 18…”
Section: Discussionmentioning
confidence: 99%
“…14 Infections can be divided into two groups: mycotic (fungal) versus non-mycotic (non-fungal) pseudoaneurysms. 15 The most common types of infective mycotic organisms include Candida albicans and Aspergillus species. 13 Non-mycotic organisms are much less common, with Psuedomonas aeruginosa and Methicillin-resistant Staphylococcus aureus (MRSA) being the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplant renal artery (TRA) pseudoaneurysm is an uncommon but potentially catastrophic vascular complication after kidney transplantation with a general incidence <1%. [1][2][3] The most common site of TRA pseudoaneurysm formation is the suture line at the arterial graft anastomosis. 2 Common causes include perivascular infections, suture rupture, poor surgical technique, anastomotic leakage, vessel-wall ischemia, or diagnostic procedures such as biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The clinical presentation of a TRA pseudoaneurysm may vary from an asymptomatic incidental finding to proteiform manifestations including graft dysfunction or loss, fever, abdominal or incisional pain, intra-abdominal or retroperitoneal bleeding, pulsatile mass, infections, malignant hypertension, anemia of unknown origin, lumbosacral plexopathy, limb ischemia, loss or thrombosis, hemorrhagic shock, sepsis, and death. 1,4,[7][8][9] Diagnosis of TRA pseudoaneurysms can be made by Doppler duplex ultrasound, catheter angiography, computed tomography (CT), or magnetic resonance (MR) angiography. 4,10 The treatment option depends on several variables including and not limited to: hemodynamic stability of the patient, pseudoaneurysm's etiology, radiological features, and size, graft function, anatomy, and presentation.…”
Section: Introductionmentioning
confidence: 99%